Prolonged Emergency Department Stay at Referring Facilities: A Poor Trauma Performance Improvement Tool. Issue 4 (April 2022) - Udekwu, Pascal; Simonson, Brian; Stiles, Anquonette; Mclntyre, Sarah; Tann, Kimberly; Schiro, Sharon
Background: Delays in the transfers of injured patients are perceived to increase morbidity and mortality and drive initiatives to limit the emergency department length of stay (LOS) at referring facilities (RF). RF LOS >4 hours is used for performance improvement (PI) with a large review burden with few improvement opportunities. Methods: A statewide trauma registry 2013-2018 was used. Descriptive and inferential statistics including logistic regression were used to evaluate nongeriatric adult patients with ED LOS <12 hours. Paired data analyses utilizing prehospital (PH) and RF variables, vital signs (VS), Glasgow Coma Score–Motor component (GCS-M), RF LOS, mortality, trauma center hospital LOS (HLOS), and intensive care unit (ICU) LOS were performed. Results: 13, 721 of 56, 702 transfer patients were selected. Mortality fell over time in all abbreviated injury score groups. GCS-M and systolic blood pressure (SBP) were correlated with mortality in both prehospital and RF data and highest in patients with abnormal GCS-M or SBP in both settings (38.0%, 30.1%). Examination of mortality over time in the group with abnormal VS showed SBP as the only variable with increasing mortality related to RF LOS. Average HLOS and ICU LOS were longest in patients with abnormal PH and RF SBP and GCS-M. Discussion: Support for PI evaluation of RF LOS >4 hours was not identified. Increased survival over time is explained by early transfers of high mortality patients. Our data support existing efficient statewide transfers and recommend PI review of transfer patients with abnormal GCS-M and SBP in a narrower timeframe.